Public Libraries: Celebrating Diversity - Chelliah, Jes; Combes, Barbara; Brown, Justin (2012)
The origin of Public libraries is grounded in equity and the advancement or enrichment of the individual. The original intention was to reduce the class divide in society and offer an equitable platform to promote values of self help to enable, facilitate and empower individuals and communities economically, socially and politically. The public library system provides access to information and community facilities for marginalized groups in populations, including low socio economic status (SES) families, the aged, people with special needs and ethnic minorities. Poor language skills in the dominant language, inadequate education, poor finances, and lack of access to computer technologies and relevant skills, hinder access to information, community facilities and life opportunities. In cases where formal education is lacking or even absent, the public library is positioned to function as an informal education conduit for facilitating lifelong learning. Strategically located in both urban and rural population centres, the seventeen hundred (1700) public libraries that make up the Australian public library network provide a viable infrastructure to enable equity of access to information, social inclusion and to influence the development of social capital in multicultural Australia. This paper will examine the research and current state of play in Australian public libraries and investigate the notion that public libraries have a role in facilitating community building for non-English speaking ethnic groups. It is part of a much larger PhD study investigating opportunities for building sustainable communities and nation building for a multicultural Australia.